Penerapan Integrated Video Tutorial Based Learning untuk Meningkatkan Kemampuan Menggunakan Alat Elektronik dengan Aman - Basten Yuni Artika (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2022)
The Minister of Education and Culture of the Republic of Indonesia on March 24, issued Circular Letter Number 4 of 2020 which contains the Implementation of Education Policies in the Emergency Period for the Spread of COVID 19. The Circular explains that the teaching and learning process is set to be carried out at home through online/distance learning. Even schools that accommodate children with special needs.The purpose of this study is to describe the process of improving learning achievement of materials using Electronic Devices Safely through the application of the Integrated Video Tutorial Based Learning learning model. The research method in the form of Classroom Action Research is an observation of learning activities in the form of an action, which is deliberately raised based on problems occurring in the classroom. The results of the study indicate that the Integrated Video Tutorial Based Learning learning model can improve learning achievement using electronic tools safely. In the pre-cycle the ability of children who succeeded only 14%. In Cycle 1 it reached 43%, in Cycle 2 it reached 86%. Recommendations for future researchers are to provide a new discourse on research, especially in the variables used. In order to be able to make the results of this study as a relevant reference towards more useful follow-up for the learning of mentally retarded students.